2007
DOI: 10.1089/oli.2007.0044
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regression of Cells Expressing Mouse Cytoskeleton-Associated Protein 2 Transcript by Trans-Splicing Ribozyme

Abstract: Cytoskeleton-associated protein 2 (CKAP2) is known to be highly expressed in primary human cancers as well as most cancer cell lines. CKAP2 functions as microtubule stabilizer and probably as cell proliferation inducer, indicating that CKAP2 might be a potential anticancer target. In this study, we developed a specific ribozyme that can replace mouse CKAP2 (mCKAP2) RNA with new transcripts through trans-splicing reaction. This specific RNA replacement resulted in triggering of transgene activity selectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Therefore, we carried out experiments using a single model mRNA substrate, and we targeted a subset of the possible splice sites on this substrate. On the other hand, the trans-tagging assay has already been successfully applied to map efficient splice sites on at least eight different mRNA substrates (Lan et al 1998;Watanabe and Sullenger 2000;Rogers et al 2002;Park et al 2003;Jung and Lee 2005;Fiskaa et al 2006;Kim et al 2007). Moreover, the proposed calculation of DG bind relies on secondary structure prediction algorithms that are very fast but not always accurate because they do not take into account all possible RNA interactions and they are sensitive to errors in experimental energy parameters (Layton and Bundschuh 2005;Condon and Jabbari 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we carried out experiments using a single model mRNA substrate, and we targeted a subset of the possible splice sites on this substrate. On the other hand, the trans-tagging assay has already been successfully applied to map efficient splice sites on at least eight different mRNA substrates (Lan et al 1998;Watanabe and Sullenger 2000;Rogers et al 2002;Park et al 2003;Jung and Lee 2005;Fiskaa et al 2006;Kim et al 2007). Moreover, the proposed calculation of DG bind relies on secondary structure prediction algorithms that are very fast but not always accurate because they do not take into account all possible RNA interactions and they are sensitive to errors in experimental energy parameters (Layton and Bundschuh 2005;Condon and Jabbari 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences from several clones are then used to deduce the positions of efficient splice sites (Jones et al 1996;Lan et al 1998;Einvik et al 2004). This trans-tagging assay has been successfully applied-without explicitly reported limitations-to uncover efficient splice sites on various mRNA substrates (Lan et al 1998;Watanabe and Sullenger 2000;Rogers et al 2002;Park et al 2003;Jung and Lee 2005;Fiskaa et al 2006;Jung and Lee 2006;Kim et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem and improve the therapeutic potential of this approach, safer, more efficient, and endogenously and exogenously regulated trans ‐splicing ribozymes are required (Figure ). Improvement of specificity of intracellular trans ‐splicing reaction and no off‐target effects were reported through 5′‐end rapid amplification of cDNA ends (RACE) PCR analysis of the total trans ‐spliced products in the target RNA‐expressing cells by the modification of ribozyme to contain EGS upstream of IGS and the P10 helix sequence (Jung & Lee, ; Kim et al, ; Kim et al, ; Kwon et al, ). Moreover, recent studies have reported the development of trans ‐splicing ribozymes for which the activities can be precisely regulated using endogenous circumstances (Kim & Lee, ) or tissue‐specific miRNAs (Kim et al, ; Won et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Won and Lee () developed an adenoviral hTERT‐targeting trans ‐splicing ribozyme in which the 3′‐exon had been exchanged with E1A, thus potentially converting a replication‐incompetent adenoviral vector to replication‐competent virus in hTERT‐expressing cells via a precise trans ‐splicing reaction. Trans ‐splicing ribozymes specific for carcinoembryonic antigen (CEA; Jung & Lee, ), cytoskeleton‐associated protein 2 (CKAP2; Ban et al, ; Kim et al, ), alpha‐fetoprotein (AFP; Won & Lee, ), and pancreatic adenocarcinoma upregulated factor (PAUF) RNA (Kim et al, ), all of which are over‐expressed in various cancers, have also been developed, and the abilities of these constructs to induce therapeutic transgene expression through target RNA reprograming have been specifically validated in target RNA‐expressing cells.…”
Section: Group I Intron Ribozymes As Therapeuticsmentioning
confidence: 99%
“…Recently, we developed trans-splicing ribozymes that targeted a variety of targets including carcinoembryonic antigen, 37 a-fetoprotein, 38 or mouse cytoskeleton-associated protein 2 transcript, 39 and demonstrated that the ribozymes both efficiently and specifically retarded the survival of cancer cells expressing the corresponding target RNA in vitro. Further in vivo evidence will indicate the general feasibility of the trans-splicing ribozyme for purposes of cancer gene therapy.…”
Section: Discussionmentioning
confidence: 99%